Graphene-Based Electrode Materials via Liquid Phase Exfoliation from Chicken Feather Waste - Negara, Vamellia Sari Indah; Usna, Sri Rahayu Alfitri; Machmudah, Machmudah; Astuti, Astuti (Universitas Andalas, 2025)
Graphene was successfully synthesized from chicken feather biomass waste using the Liquid Phase Exfoliation (LPE) method assisted by Linear Alkylbenzene Sulfonate (LAS) surfactant at varying volumes of 1 mL, 1.5 mL, and 2 mL. The aim of this study was to evaluate the potential of chicken feather-derived graphene as an electrode material for rechargeable batteries. Characterization using UV-Visible spectrophotometry showed a distinct absorption peak at approximately 270 nm, corresponding to the π→π* electronic transition, with increasing absorbance intensity observed with higher surfactant volumes, indicating more effective graphene exfoliation. XRD analysis revealed a shift in diffraction peaks to lower 2 angles, increased interlayer spacing (d-spacing), and the largest crystallite size of 13.58 nm at a surfactant volume of 1.5 mL. These results indicate that the surfactant plays a critical role in stabilizing and forming the crystalline structure of graphene. Overall, this study demonstrates that chicken feather-based graphene has promising potential to be developed as an eco-friendly electrode material in rechargeable battery applications